Correlation of Parent’s Educational Level and Learning Motivation on Thematic Learning Outcomes of Class VI Students of SD Negeri 1 Panjilor - Abdul Wahid; Joko Waluyo; Mohammad Imam Farisi (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine the correlation between parental education level and learning motivation with thematic learning outcomes of class VI students at SD Negeri 1 Panji Lor. This research uses quantitative analysis methods. The subjects of this research involved 38 class VI students at SD Negeri 1 Panji Lor. The normality and homogeneity tests were carried out to produce a good sample. Data collection instruments include questionnaires and written tests. Before use, the instrument is tested for validity and reliability to ensure that the instrument can be used appropriately. Hypothesis testing using simple correlation. The research results report that (1) there is a positive correlation between the level of education and learning outcomes, (2) there is a positive correlation between the level of education and learning outcomes, (3) there is a joint positive correlation between the level of education and motivation towards learning outcomes.